PENGARUH MEROKOK SIGARET PADA PEMERIKSAAN RESISTEN ASPIRIN - D.I.S Siregar; Z. Lubis; H. Hariman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Based on the Framingham study, it was revealed that cigarette smoking can cause athero- thrombotic cardiovascular disease (CVD).Aspirin is the most widely used anti platelet drug in CVD; it reduces the risk of the secondary events by about 25% in cardiovasculardisease. Lately, it was reported that 5–45% of these patients are resistant to aspirin. The researchers aimed to investigate in this study theimpact of cigarette smoking on aspirin resistance. Twenty two smokers and 18 non-smokers were enrolled in this study. The researchersrequired all of the 40 subjects to take 160 mg of aspirin after the first blood sample was taken. The first sample was taken in the morning,while the second one was obtained two (2) hours after the aspirin intake. Platelet aggregation was performed using a light transmittanceaggregometry (LTA). Aspirin resistance was found in two (2) of 22 smokers (9.09%) and two (2) of 18 non-smokers (11.11%). There wereno significant differences (p>0.05) before or after taking aspirin in either both smokers or non smokers as seen from the aggregationresults. The researchers concluded that cigarette smoking does not cause aspirin resistance at all.